Critical reflection workshops and knowledge exchange: findings from a Scottish project. Issue 4 (25th September 2014) - Cree, Viviene E.; Macrae, Rhoda; Smith, Mark; Knowles, Nancy; O'Halloran, Susan; Sharp, Douglas; Wallace, Elaine
Abstract: In 2013, academics from a Scottish university came together with social work managers and practitioners from two local authorities (LAs) in Scotland to run a knowledge exchange (KE) project co‐sponsored by the Economic and Social Research Council and the LAs. The project's aim was an ambitious one: to contribute to culture change in the children and families' departments in the two partner agencies. The project grew out of an earlier KE venture that had explored ways of engaging better with involuntary service users in social work; it thus both anticipated and reflected wider concerns about services for children that were also demonstrated in Munro's Review of Child Protection . The KE project had three components: training for managers, practitioner research projects and critical reflection workshops. Whether, and to what degree, the KE project changed culture is not the focus of this paper, which is written jointly by academic researchers and practitioners. Instead, one element of the KE project, namely the critical reflection workshops, is discussed. Findings provide strong evidence of the pressures currently experienced by children and families' services in the UK public sector. They also indicate how important good relationships are in building meaningful KE.